2006
DOI: 10.1590/s0100-06832006000400006
|View full text |Cite
|
Sign up to set email alerts
|

Estímulo no crescimento e na hidrólise de ATP em raízes de alface tratadas com humatos de vermicomposto: II - Efeito da fonte de vermicomposto

Abstract: RESUMOUm dos fatores mais limitantes para a produção de vermicomposto é a disponibilidade de esterco. Neste trabalho, foi avaliado o efeito da substituição parcial do esterco por bagaço de cana e por resíduos de leguminosa (Gliricidia sepium) na vermicompostagem sobre a qualidade do vermicomposto e sobre a bioatividade dos humatos, avaliadas por meio da análise do crescimento radicular e da atividade das bombas de H + isoladas de raízes de alface. A substituição do esterco por bagaço de cana e por resíduos de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
10
0
3
Order By: Relevance
“…Auxins activate the H + -ATPase of the plasma membrane, acidifying the apoplast and activating enzymes that act directly on the cell wall, allowing greater plasticity of this, leading to cell elongation (Aguirre et al, 2009;Quaggiotti et al, 2004;Rodda et al, 2006;Schiavon et al, 2010;Silva et al, 2011a;Zandonadi et al, 2007). Plant growth enhancement may also be due to the presence of polyamines, such as putrescine, spermidine and spermine found in HS (Young & Chen, 1997), that act as growth regulators of plants (Kumar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxins activate the H + -ATPase of the plasma membrane, acidifying the apoplast and activating enzymes that act directly on the cell wall, allowing greater plasticity of this, leading to cell elongation (Aguirre et al, 2009;Quaggiotti et al, 2004;Rodda et al, 2006;Schiavon et al, 2010;Silva et al, 2011a;Zandonadi et al, 2007). Plant growth enhancement may also be due to the presence of polyamines, such as putrescine, spermidine and spermine found in HS (Young & Chen, 1997), that act as growth regulators of plants (Kumar et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the use of humic substances (HS) has been proposed as a viable alternative (Calvo et al, 2014). Quaggiotti et al, 2004), auxine-like effects (Quaggiotti et al, 2004;Rodda et al, 2006;Zandonadi et al, 2007), increased concentration of chlorophyll (Baldotto et al, 2009;Ertani et al, 2011) and net photosynthesis (Canellas et al, 2002;) are the most commonly reported effects of HS on plants. The use of HS also has effect on the quality of crops, affecting concentrations of solids and soluble sugars (Lima et al, 2011), carbohydrates (Aminifard et al, 2012) and starch (Canellas et al, 2002;Ertani et al, 2011;Nardi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in absorption rates can be explained by the activation of H + -ATPase present in the plasma membrane FAÇANHA, 2004), acting on two mechanisms essential to plant growth, through the energy supply to the secondary systems in the translocation of ions and by increasing plasticity of the cell wall, thus allowing cell growth and division (RODDA et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Rodda et al (2006) verificaram que os humatos produzidos a partir de esterco bovino e da mistura esterco bovino associado ao bagaço de cana-de-açúcar proporcionaram estímulos significativos no crescimento radicular das plantas de alface. Trannin, Siqueira e Moreira (2007), ao cultivarem milho com doses crescentes de biossólido, observaram alterações na matéria orgânica e melhoria na maioria das características biológicas relacionadas à fertilidade do solo.…”
Section: Introductionunclassified